2009
DOI: 10.1001/archgenpsychiatry.2009.85
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and Adolescent Psychiatric Disorders as Predictors of Young Adult Disorders

Abstract: Context Most adults with a psychiatric disorder first met diagnostic criteria during childhood and/or adolescence, yet specific homotypic and heterotypic patterns of prediction have not been firmly established. Objective To establish which childhood and adolescent psychiatric disorders predict particular young adult disorders when accounting for comorbidities, disaggregating similar disorders, and examining childhood and adolescent predictors separately. Design/Setting/Patients Eleven waves of data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
562
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 748 publications
(607 citation statements)
references
References 60 publications
31
562
2
12
Order By: Relevance
“…Thus, depression during adolescence increases the likelihood for depression as an adult. 24,25 Given the impact of depression on adolescent outcomes (including health), the US Preventative Task Force recommended screening adolescents for depression when adequate systems are in place to ensure accurate diagnosis and treatment. 26 Early detection of depressed symptoms makes referral for formal evaluation possible and has shown to be effective in pediatric primary care settings.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, depression during adolescence increases the likelihood for depression as an adult. 24,25 Given the impact of depression on adolescent outcomes (including health), the US Preventative Task Force recommended screening adolescents for depression when adequate systems are in place to ensure accurate diagnosis and treatment. 26 Early detection of depressed symptoms makes referral for formal evaluation possible and has shown to be effective in pediatric primary care settings.…”
Section: Resultsmentioning
confidence: 99%
“…Further, patients with active IBD had signifi cantly more symptoms of depression than did patients who were in remission ( 25 ). Epidemiologic studies have indicated that an early onset of mental health disorders (e.g., anxiety and depression disorders) predicts poor long-term outcomes and chronic, recurrent mental health disorders in young adulthood and adulthood ( 26,27 ). Th e objectives of this retrospective cohort study were to estimate the risks of developing depression and anxiety disorders in young patients who were diagnosed with CD compared with matched healthy controls.…”
Section: Increased Risks Of Developing Anxiety and Depression In Younmentioning
confidence: 99%
“…However, this may partially explain why CD is associated with an increased risk of developing anxiety disorders. Mental health disorders in childhood and adolescence may predict worse long-term mental health and well-being ( 26,27 ). Longitudinal studies have shown that anxiety or depression during adolescence predict a two-to threefold increase in the risks of developing recurrent anxiety or depression in adulthood ( 41 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Adolescent-onset depression most often has a chronic, episodic course which continues into adulthood and is associated with substantial life-long morbidity (Copeland, Shanahan, Costello, & Angold, 2009;Weissman, Wolk, Goldstein, Moreau, Adams & Greenwald, 2000;Weissman, Wolk, Wickramaratne, Goldstein, Adams & Greenwald, 1999).…”
mentioning
confidence: 99%